Studi Keterdapatan Unsur Tanah Jarang REE Ce dan Y pada Berbagai Kolong di Pulau Bangka - Irvani Irvani; Janiar Pitulima (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2017)
Rare earth element REE is very potential future prospect mineral resources in Bangka Island, hence awell developed REE must have a high economic value in the future. As one of the biggest region thatproducing tin ore mining (cassiterite) for hundreds of years, REE potential not yet explored andexploited well until now days in Bangka Island, and was left abundant in ex-mining area. They carriedout from the tin ore mining and become mine waste or tailing and then through the stream flows to besuspension or bed load sediment. The aim of this study is to identify the present rare earth Ce and Ybased on shallow surface sediment samples and their spatial distribution from a number of mineponds called kolong. Primary data collection of shallow surface sediments has been collected onKolong Argotirto and Menjelang West Bangka District, Kolong PLN and Merawang in Bangka District,Kolong Rentensi Kacang Pedang and Pedindang in Pangkalpinang City. Geochemical sedimentsanalysis just for identification the presence of rare earth Ce and Y. Rare earth element of cerium(Ce) just presence in a few sample sediment, but for yittrium (Y) almost presence at all shallowsurface sediment 0,9 - 31,6 ppm. The spatial distribution of rare earth Ce and Y show heterogeneity inlaterally.